"I'm a runner not a smoker": Changes in identity as predictors of smoking cessation and physical activity. (July 2020) - Priebe, Carly S.; Beauchamp, Mark; Wunderlich, Kelly; Faulkner, Guy
Abstract: This study examined associations of changes in identity with physical activity and smoking within Run to Quit, a national multiple health behaviour change intervention that utilizes group-based learn-to-run clinics to assist participants in quitting smoking. It was hypothesized that the behaviour-change curriculum and running delivered via groups, would not only help participants mitigate physical symptoms of withdrawal but would also facilitate changes in smoking- and running-related identities. Further, changes in these identities (i.e., reduced smoker identity and increased runner identity) were hypothesized to predict smoking cessation and running behaviour. Adult smokers ( n  = 216) completed 10-week clinics in Running Room locations across Canada. Within the pre-post design, participants completed questionnaires assessing identity, physical activity, running frequency, and smoking status (including carbon monoxide [CO] testing) at weeks 1 and 10, as well as post-program interviews. Consistent with a priori hypotheses, runner identity increased, and smoker identity decreased from beginning to end of program ( p 's<.001). Regression analyses indicated that reductions in smoker identity predicted reductions in CO levels (β = 0.302, p  < .001) and increases in runner identity predicted increases in running frequency (β = 0.235, p  = .001). While change in runner identity was correlated with quit outcomes and change in smoker identity correlated with running frequency ( p 's<.001), they were not significant predictors in the other behaviour models, and neither was the interaction between the two identities. Although future experimental research is required, these findings, along with complimentary qualitative data, suggest changes in identity may be one potential avenue through which group-based physical activity assists smoking cessation. Highlights: activity-based smoking cessation interventions may serve to influence variables such as identity. Runner and smoker identity significantly changed over the course of this 10-week intervention. Changes in runner identity predicted end of program run outcomes. Changes in smoker identity predicted end of program cessation outcomes.